Frege, Gottlob; Gabriel, Gottfried (ed.), „Vorlesungen über Begriffsschrift“, History and Philosophy of Logic 17, No. 1 (1996), iii–xvi, 1–48 - Peckhaus, Volker (zbMATH Open, Zbl. 0860.01036)

Jourdain, P.E.B., Selected Essays on the History of Set Theory and Logics (1906–1918), hg. v. I. Grattan-Guinness, CLUEB: Bologna 1991 - Peckhaus, Volker (zbMATH Open, Zbl. 0853.01037)

Temple, George, “Fundamental Mathematical Theories”, Philos. Trans. R. Soc. Lond., Ser. A 354, No. 1714 (1996), 1941–1967 - Peckhaus, Volker (zbMATH Open, Zbl. 0863.03005)

DePauli-Schimanovich, Werner/Weibel, Peter. Kurt Gödel: ein mathematischer Mythos, Hölder-Pichler-Tempski: Wien 1997 - Peckhaus, Volker (zbMATH Open, Zbl. 0872.01030)

Gödel, Kurt, Unpublished Philosophical Essays, hg. v. Francisco A. Rodríguez-Consuegra, Birkhäuser: Basel 1995 - Peckhaus, Volker (zbMATH Open, Zbl. 0854.01046)

Halmos, P.R., “To Count or to Think, that is the Question”, Nieuw Arch. Wiskd., IV. ser., 13 (1995), 61–76 - Peckhaus, Volker (zbMATH Open, Zbl. 0858.00006)

Hintikka, Jaakko, The Principles of Mathematics Revisited, Cambridge University Press: Cambridge 1996 - Peckhaus, Volker (zbMATH Open, Zbl. 0869.03003)

Benmakhlouf, Ali. Gottlob Frege. Logicien philosophe, Presses Universitaires de France: Paris 1997 - Peckhaus, Volker (zbMATH Open, Zbl. 0873.01015)

Logik, Mathesis universalis und allgemeine Wissenschaft. Leibniz und die Wiederentdeckung der formalen Logik im 19. Jahrhundert - Peckhaus, Volker
Rezensionen: J. Legris, “Mathesis Universalis”, Mathesis 13 (1997), 167– 175; Zbl. Math. 884.01021 (R. Murawski); Philosophischer Literaturanzeiger 51 (1998), 114–117 (G. Schenk); MR 98h:01013 (H. Sinaceur); Peirce Project Newsletter 3 No. 1, 7; Philosophiegeschichte und logische Analyse. Logical Analysis and History of Philosophy, Bd. 2, Mentis: Paderborn 1999, 259–264 (W. Malzkorn); History and Philosophy of Logic 20 (1999), 67–69 (H. Linneweber-Lammerskitten); Erkenntnis 50 (1999), 133–136 (P. Mancosu); Berichte zur Wissenschaftsgeschichte 22 (1999), 207–208 (P. Mancosu); NTM. Schriftenreihe für Geschichte der Naturwissenschaften, Technik und Medizin N.S. 8 (2000), H. 1, 290 (K.-H. Schlote), 49–50; Anuario Filosofico 32 (1999), 853–854; M.F., “La logica di Leibniz nel XIX secolo”, Giornale critico della filosofia Italiana 6 ser. 20 (2000), 161–164; Archiv für Geschichte der Philosophie 82 (2000), 349–352 (R. Vilkko); Epistemologia 24 (2001), 152–155 (M. Ferriani); The Review of Modern Logic 9, nos. 3 & 4 (2003–2004), 119–122 (H. Frank).

The Varieties of Understanding: English Philosophy since 1898 - Milkov, Nikolay

The Varieties of Understanding: English Philosophy since 1898 - Milkov, Nikolay

Causal Symmetric Spaces, Geometry and Harmonic Analysis - Hilgert, Joachim; Ólafsson, Gestur

Blinde Flecken in der Berufsorientierung im Rahmen der Arbeitslehre. Zusammenhang von Erwerbsarbeit und Hausarbeit fehlt nach wie vor. - Bigga, Regine (Hauswirtschaftliche Bildung)

Doktorandinnenkolleg Erkenntnisprojekt Feminismus – Theoretische und empirische Studien zur Frauenforschung an der Universität Bremen - Weber, Jutta (Die Philosophin 16/1997)

Sprechen wovon sich nicht sprechen läßt? Zum Naturbegriff in der aktuellen feministischen Debatte - Weber, Jutta (Feministische Studien 2/1997)

A Visual Programming Language for Qualitative Data - Dücker, M.; Geiger, Christian; Lehrenfeld, Georg; Müller, Wolfgang; Tahedl, C. (Proceedings of the 1997 IEEE Symposium on Visual Languages)
Modeling of human knowledge and reasoning requires the formulation of uncertainty in its various forms. Fuzzy logic was introduced to directly support these applications (H. Zimmermann, 1991). Fuzzy control (FC) which is based on fuzzy logic allows one to control complex systems based on qualitative information like human knowledge (C. Geiger and G. Lehrenfeld, 1994). In fuzzy logic, fuzzy sets are usually defined and manipulated by means of complex mathematics, whereas the fuzzy control process is frequently outlined by visual sketches based on set diagrams in order to enhance the comprehension of the inference process. The rule based execution of this process usually follows the lines of rule based visual programming languages (VPLs), i.e., languages comparable to Agentsheets and ChemTrains. This strongly indicates that VPLs are thus well applicable for this use. We first outline the basic concepts of fuzzy logic and fuzzy control. Thereafter, we sketch a visual language which integrates fuzzy set diagrams in the visual representation of rules. The basic concepts are inherited from the complete visual programming language, Pictorial Janus (PJ). However, we significantly simplify PJ's visual concepts in order to adapt it for our purpose.
Keywords: Computer languages; Fuzzy control; Fuzzy sets; Animation; Visualization; Fires; Application software; Pattern matching; Impedance matching; Domain specific languages

“Der Körper hat es dann auszubaden...” – zum Verhältnis von Körper, Sprache und (Re)Produktivität bei Unica Zürn - Morrien, Rita (Freiburger FrauenStudien – Zeitschrift für Interdisziplinäre Frauenforschung)

Optical storage effect in a discotic columnar liquid crystal - FORGET, SANDRINE; Kitzerow, Heinz-Siegfried (Liquid Crystals)
Keywords: Condensed Matter Physics; General Materials Science; General Chemistry

Optical network analyzer applied for fiber Bragg grating characterization - Sandel, D; Noé, Reinhold (IOOC-ECOC 97 - 11TH INTERNATIONAL CONFERENCE ON INTEGRATED OPTICS AND OPTICAL FIBRE COMMUNICATIONS / 23RD EUROPEAN CONFERENCE ON OPTICAL COMMUNICATIONS, VOL 3)

Optical network analyzer applied for fiber Bragg grating characterization - Sandel, D; Noé, Reinhold (IOOC-ECOC 97 - 11TH INTERNATIONAL CONFERENCE ON INTEGRATED OPTICS AND OPTICAL FIBRE COMMUNICATIONS / 23RD EUROPEAN CONFERENCE ON OPTICAL COMMUNICATIONS, VOL 3)